Organic cotton in demand - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Cotton grown organically without the use of pesticides is selling at higher prices than the conventionally grown fibre, and the demand is increasing every year. Over 10 000 tonnes are now being produced in South America, Egypt and India. Most of...